A Tisket, a Tasket: Basketing and Corporate Tax Shelters - Leandra Lederman (Washington University Law Review, 2011)
In an income tax system that comported with the economic, or Haig-Simons, definition of income, deductible expenses would not face sourcebased limitations. A true Haig-Simons income tax system therefore would not take the schedular approach of sorting different types of expenses and losses into distinct conceptual “baskets” containing corresponding types of income. Practical realities often require departing from the Haig-Simons norm, however. The U.S. federal income tax system does require individuals to basket a number of types of expenses and losses. For example, individuals’ passive activity losses can only be deducted from passive income gains. By contrast, most corporations taxed under Subchapter C of the Internal Revenue Code are not subject to many of these restrictions. Thus, corporations generally can deduct their passive investment expenses and losses from their active business income. That ability allowed the creation of infamous tax strategies such as Son-of-BOSS and the CINS contingent installment sale shelter. In order to prevent the resurgence of abusive tax shelters, this Article proposes to extend to the domestic corporate context the passive/active distinction that already exists for individuals. If corporations were required to basket their passive-source expenses and losses with their passive income (such as income from interest, dividends, and rents and royalties, other than those produced by an active business), many abusive tax shelters involving financial products would not work. The Article also considers the three principal objections to the proposal—that it is overbroad, underinclusive, and too complex—and argues that the proposal is tailored so as to minimize these costs.
Keywords: Income tax deductions for losses; Tax shelters; Income tax; Passive activity losses; Foreign tax credit